The Effect of Fatigue on the Postural Balance of Young Women Using Electromyography of Lower Extremity Muscles - Afsaneh Ghodsi; Sadegh Naserkhaki; Ali Tanbakoosaz (Biyumikānīk-i varzishī)
Objective: This study aimed to examine the effect of fatigue on postural balance of young women using Electromyography (EMG) of lower extremity muscles and measuring the foot plantar Center of Pressure (COP) displacement. Methods: Participants were 10 young women (mean age, 26.4±3.01 years; mean weight, 65.5±5.75 kg; mean height, 165±2.61; BMI, 24.08±2.08 kg/m2) with no history of lower limb injury or balance problems. To evaluate their static balance, the stork test was used and the foot plantar COP was measured by force plates. To measure fatigue, three parameters of muscle power (P), median frequency of muscle (F) and Root Mean Square (RMS) of raw EMG signals were calculated. Data were analyze din SPSS V. 16 and MATLAB software using Mann-Whitney U test. Results: fatigue had a significant effect on P and RMS parameters (P<0.05), but did not significantly affect the F. It increased P and decreased RMS. The highest change in the P parameter was seen in biceps femoris muscle; the highest change in the F parameter was related to semitendinosus muscle; and the highest change in the RMS parameter was related to gastrocnemius lateralis and gastrocnemius medialis muscles. Conclusion: There is a negative relationship between fatigue of the lower extremity muscles and balance impairment; by increasing the level of fatigue in the muscles, balance is more impaired.